New Methods, Old Brains—A Systematic Review on the Effects of tDCS on the Cognition of Elderly People - Siegert, Anna; Diedrich, Lukas; Antal, Andrea (Frontiers in Human Neuroscience, 2021)
The world’s population is aging. With this comes an increase in the prevalence of age-associated diseases, which amplifies the need for novel treatments to counteract cognitive decline in the elderly. One of the recently discussed non-pharmacological approaches is transcranial direct current stimulation (tDCS). TDCS delivers weak electric currents to the brain, thereby modulating cortical excitability and activity. Recent evidence suggests that tDCS, mainly with anodal currents, can be a powerful means to non-invasively enhance cognitive functions in elderly people with age-related cognitive decline. Here, we screened a recently developed tDCS database (http://tdcsdatabase.com) that is an open access source of published tDCS papers and reviewed 16 studies that applied tDCS to healthy older subjects or patients suffering from Alzheimer’s Disease or pre-stages. Evaluating potential changes in cognitive abilities we focus on declarative and working memory. Aiming for more standardized protocols, repeated tDCS applications (2 mA, 30 min) over the left dorso-lateral prefrontal cortex (LDLPFC) of elderly people seem to be one of the most efficient non-invasive brain stimulation (NIBS) approaches to slow progressive cognitive deterioration. However, inter-subject variability and brain state differences in health and disease restrict the possibility to generalize stimulation methodology and increase the necessity of personalized protocol adjustment by means of improved neuroimaging techniques and electrical field modelling.